Risk Factors for Coracoid Graft Osteolysis after the Open Latarjet Procedure - Marcio Cohen; Alexandre Dreifus Zaluski; Glaucio Sales de Lima Siqueira; Marcus Vinicius Galvão Amaral; Martim Teixeira Monteiro; Geraldo Rocha Motta Filho (Revista Brasileira de Ortopedia)
Abstract Objective Coracoid osteolysis has been described as a possible complication after the Latarjet procedure. The aim of the present study was to investigate the incidence and risk factors associated to coracoid graft osteolysis and to correlate them with clinical results. Methods A retrospective review of 38 Latarjet procedures was conducted. Computed tomography (CT) scans were obtained from all of the patients before and at least 1 year after the surgery. Coracoid osteolysis was evaluated and correlated to preoperative factors, namely: age, smoking status, and preoperative glenoid bone loss. The patients were divided into 2 groups: A (no or minor bone resorption) and B (major or total bone resorption). The functional outcome was determined by the Rowe score. Results Coracoid graft osteolysis occurred in 22 cases (57.8%). The mean preoperative glenoid defect was 22.8% in group A, and 13.4% in group B (p= 0.0075). The mean ages of the subjects in both groups were not significantly different. Smoking did not seem to affect the main outcome either, and no correlation was found between graft osteolysis and postoperative range of motion, pain, or Rowe score. There were no cases of recurrent dislocations in our sample, although four patients presented with a positive anterior apprehension sign. Conclusion Bone resorption of the coracoid graft is present in at least 50% of the patients submitted to the Latarjet procedure, and the absence of significant preoperative glenoid bone loss showed to be the only risk factor associated with severe graft osteolysis, even though this did not influence significantly the clinical outcome.